CHRONIC RHINITIS INDUCED BY BACTERIAL INFECTION IN A CAT - Nevi,; Widyastuti, Sri Kayati; Suartha, I Nyoman (Buletin Veteriner Udayana, 2025)
Rhinitis is a respiratory disease that causes inflammation of the nasal mucosa. This article aims to identify the results of anamnesis, clinical symptoms, and supporting examination results in a cat case to determine the diagnosis and evaluate the provided therapy. The case subject is a pet cat named Putih, female, 1 year old, weighing 3 kg, came with complaints of a runny nose and sneezing that had lasted for approximately 1 month. On physical examination, mucopurulent discharge was seen in both noses, ulcers in the mouth, and sneezing. In supporting examinations such as routine hematological, radiography, calicivirus test kit, cell cytology, and bacterial culture were carried out. The results of the bacterial culture showed the presence of Streptococcus sp. bacteria. The case cat was diagnosed with rhinitis caused by Streptococcus sp. bacterial infection with a fausta prognosis. Treatment was carried out by administering antibiotics doxycycline (5 mg/kg, twice a day PO), meloxicam (0.1 mg/kg, once a day PO), antihistamine chlorphenamine maleate (2 mg/cat, once a day PO), and vitamin B complex (once a day PO). Two weeks after therapy, the cat began to improve, indicated by the absence of any more runny nose, no more sneezing, and the ulcers began to improve. During therapy, the cat must be supervised by the owner, so that the condition can always be controlled